Nature as a Classroom: A Strategic Evaluation of Forest Parks as Authentic Geography Learning Resources - Daudi Richard Malusu; Blessing Chenaimoyo Shanduka; Zunaira Algy Jamen; Lingga Zuama Firdyan; Rio Rifaldi (Future Space: Studies in Geo-Education, 2026)
Precet Forest Park (PFP) is a unique community-based tourism destination that integrates forest conservation with active production functions, such as resin tapping and coffee cultivation. This study evaluates the strategic position of PFP to formulate a sustainable development model, specifically operationalizing its role as an authentic learning resource for geography education. A descriptive mixed-methods framework was employed, synthesizing qualitative insights from in-depth interviews and field observations into quantitative Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices. To ensure methodological rigor and mitigate subjectivity, weights and ratings were assigned through a triangulated expert judgment process involving consensus with the LMDH Wana Lestari management. Quantitative evaluation identifies a robust internal index (IFAS: 4.13) against an external score of 2.25. However, these metrics are underscored by a critical threat intensity of 4.27, primarily stemming from acute regional destination competition and inherent geophysical vulnerabilities such as landslide risks. Consequently, the site is situated within Quadrant II of the SWOT matrix. The findings dictate a diversification strategy, rebranding the site as an educational outdoor laboratory to mitigate external pressures. This approach aims to optimize the park’s function as an authentic learning resource designed to support students' spatial intelligence and disaster mitigation awareness. Ultimately, this strategic shift ensures the destination's long-term economic viability and ecological sustainability through structured pedagogical innovation, effectively bridging the gap between classroom theory and socio-spatial realities to enhance geographic literacy.